Eksplorasi Nilai-Nilai Ekoliterasi dalam Buku Pelajaran Tematik Sekolah Dasar Kelas Tinggi - Dwi Kurniasih (Balai Bahasa Provinsi Riau, 2022)
The high intensity of human interaction with nature results in increasingly severe environmental damage. Many environmental damages are caused by some individuals’ lack of ecological awareness . This study aims to explore the ecological literacy values ​​contained in the thematic teaching materials of upper grades in elementary school covering 4th, 5th, and 6th grades implementing the 2013 curriculum. The focus of the problem lies in the forms of ecological literacy values ​​contained in the textbooks and how the values were ​​distributed. The method used in this research is descriptive qualitative and the approach is content analysis. The data sources were three thematic learning books used in upper elementary grades (4th,5th,an 6th) implementing the 2013 curriculum. The results showthat the entire books contain eco-literacy values, namely, knowledge, attitudes, behaviors, and cognitive skills. The value whose percentage is the highest is the knowledge. The three books do not make available a balanced component of literacy values and do not emphasize the material in the entire components. Knowledge value is not sufficient in terms of environmental protection and improvement and environmental literacy as well. The balance of the entire eco-literacy values in the thematic learning books of upper elementary school is needed to grow and create competent human beings in maintaining, caring for, and preserving the environment properly and correctly.